2009
DOI: 10.1016/j.neubiorev.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreceptors and thermosensitive afferents

Abstract: Cutaneous thermosensation plays an important role in thermal regulation and detection of potentially harmful thermal stimuli. Multiple classes of primary afferents are responsive to thermal stimuli. Afferent nerve fibers mediating the sensation of non-painful warmth or cold seem adapted to convey thermal information over a particular temperature range. In contrast, nociceptive afferents are often activated by both, painful cold and heat stimuli. The transduction mechanisms engaged by thermal stimuli have only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 86 publications
2
96
0
1
Order By: Relevance
“…4A–B). Type I cold sensors responded tonically to mild cooling but quickly inactivated when temperature dropped below the innocuous range (~20° C; Fig 4C–D); these are hallmarks of the classically defined cold receptors (Hensel and Zotterman, 1951; Schepers and Ringkamp, 2009) (see Fig S5 for a larger sampling of temperatures). Although the activity of type I neurons can robustly signal mild cooling temperatures (>20° C), given their rapid silencing during persistent noxious cold we wondered what sensory populations allow the organism to remain responsive to noxiously cold temperatures?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A–B). Type I cold sensors responded tonically to mild cooling but quickly inactivated when temperature dropped below the innocuous range (~20° C; Fig 4C–D); these are hallmarks of the classically defined cold receptors (Hensel and Zotterman, 1951; Schepers and Ringkamp, 2009) (see Fig S5 for a larger sampling of temperatures). Although the activity of type I neurons can robustly signal mild cooling temperatures (>20° C), given their rapid silencing during persistent noxious cold we wondered what sensory populations allow the organism to remain responsive to noxiously cold temperatures?…”
Section: Resultsmentioning
confidence: 99%
“…Studies beginning nearly a century ago demonstrated the existence of diverse cutaneous nerve endings sensitive to cooling or heating. These include both dedicated thermosensors as well as polymodal neurons activated by thermal, mechanical, and/or chemical stimuli (Schepers and Ringkamp, 2009). A transformative advance in our understanding of pain and thermosensation came with the seminal discovery of a set of members of the TRP family of ion channels activated by both chemical irritants and temperature(Julius, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with the finding of the present study with male rats, but the reason for a lack of hyperalgesia in sham females is not clear. One explanation for male sham differences may relate to thermosensitive TRPV channels that are expressed in sensory neurons and that detect distinct temperature thresholds in both humans and mice (Smith et al, 2002; Moqrich et al, 2005; see Dhaka et al, 2006, and Schepers and Ringcamp, 2010 for review). Recent ongoing work showed that male rats had a greater preference and sensitivity for temperature differences compared to females, possibly due to differences in sensitivity of TRP channels (Carstens et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In higher organisms, skin forms a protective layer that enables the body to detect changes in the physical, chemical, and thermal environment (Schepers & Ringkamp, 2009). A wide array of specialized sensory neurons that specifically detect and transduce thermal changes over a broad range of temperatures innervate skin (McGlone & Reilly, 2010; Schepers & Ringkamp, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of specialized sensory neurons that specifically detect and transduce thermal changes over a broad range of temperatures innervate skin (McGlone & Reilly, 2010; Schepers & Ringkamp, 2009). These sensory neurons are activated at distinct temperature thresholds and allow organisms to differentiate between noxious cold (<15 °C) and heat (>43 °C), and pleasant cool (15–25 °C) and warm (30–40 °C) (Figure 7.1) (McKemy, 2013).…”
Section: Introductionmentioning
confidence: 99%